Clinico-epidemiological study on metal-induced contact dermatitis from North India - Singh, Khushman; Gupta, Sunil Kumar; Gupta, Veenu; Brar, Sukhmani Kaur (Journal of Pakistan Association of Dermatologists, 2016)
Objective To determine the prevalence of metal sensitization and different clinical patterns in suspected patients of metal induced contact dermatitis. Methods This was an epidemiological study during which a total of 100 patients suspected and provisionally diagnosed as having contact dermatitis to metals were subjected to a patch test with Indian Standard Battery developed by CODFI (Contact and Occupational Dermatoses Forum of India). Results were read after 48hrs of application and a second reading, if required, was taken after 72-96hrs. Results Most of the patients in this series presented with hand eczema (40%), which was followed by dermatitis localized to site of contact with metal (20%) and facial dermatitis including eyelid dermatitis (15%). Twenty-seven patients showed positive reactions to metal allergens. Cross-sensitivity was low and three patients or 11.11% showed sensitization to two metal allergens. No patient showed sensitization to all the three metals. Conclusion Nickel was the commonest metal allergen identified and it was relevant in 100% of the cases. It showed a strong female preponderance. Patch testing is hence a helpful diagnostic aid in identifying the agents responsible for contact dermatitis and a sincere effort should be made to determine clinical relevance of the test results in every case.